Rebuilding Education: STEM Education Practices and Research during the Post-COVID-19 Era (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the impact of the global COVID-19 pandemic on STEM education and measures (teaching tools and research practices) taken to combat the learning gaps in STEM education in the post-pandemic era. Contributions were collected from researchers engaged in STEM education research, including the methods, pedagogical approaches, and environments they utilize in the post-pandemic era.